Pelaksanaan Eksekusi Jaminan Fidusia Pasca Putusan MK NO: 18/ PUU-XVII/ 2019 dan PUTUSAN MK NO: 2/ PUU-XIX/2021 (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
This research aims to provide an overview of the execution of the fiduciary security object following the read of the two Constitutional Court Decisions which altered the understanding of the legal norms for the execution of the fiduciary security. The research method used is a normative juridical research method. The novelty of this article is related to the new legal norms in the execution of fiduciary guarantees related to the implementation of executive titles on fiduciary guarantee certificates and parate executive as well as the researcher's views which contradict the legal considerations and legal orders of the Constitutional Court in both decisions. Subsequent to the enactment of the two Constitutional Court Decisions, the creditor as the fiduciary recipient cannot immediately perform the execution of the object of the fiduciary security belonging to the debtor as the fiduciary recipient in the event that the debtor does not agree to the breach of contract and the debtor refuses to submit the object of the fiduciary guarantee voluntarily to the creditor. In addition, the legal norms contained in the two decisions of the Constitutional Court are a form of affirmation of the legal norms that should be carried out by creditors in carrying out the executorial title in a fiduciary guarantee certificate, namely by submitting an application for the execution of the object of guarantee to the Head of the local District Court.